2000
DOI: 10.1182/blood.v95.7.2321.007k33_2321_2328
|View full text |Cite
|
Sign up to set email alerts
|

A novel nuclear phosphoprotein, GANP, is up-regulated in centrocytes of the germinal center and associated with MCM3, a protein essential for DNA replication

Abstract: Antigen (Ag) immunization induces formation of the germinal center (GC), with large, rapidly proliferating centroblasts in the dark zone, and small, nondividing centrocytes in the light zone. We identified a novel nuclear protein, GANP, that is up-regulated in centrocytes. We found that GANP was up-regulated in GC B cells of Peyer's patches in normal mice and in spleens from Ag-immunized mice. GANP-positive cells appeared in the light zone of the GC, with coexpression of the peanut agglutinin (PNA) (PNA)-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We hypothesized that one or several RNA processing or export factors might be recruited to the NPC in TPR-dependent manner in order to perform their function. To address this, we processed NPC-enriched protein extracts by mass spectrometry and found a reduction of GANP 35 and PCID2 subunits of TREX-2 complex in TPR-depleted cells but not in NUP153- or NUP50-depleted cells (Fig. 3c and Supplementary Data 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that one or several RNA processing or export factors might be recruited to the NPC in TPR-dependent manner in order to perform their function. To address this, we processed NPC-enriched protein extracts by mass spectrometry and found a reduction of GANP 35 and PCID2 subunits of TREX-2 complex in TPR-depleted cells but not in NUP153- or NUP50-depleted cells (Fig. 3c and Supplementary Data 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note with regard to the patient´s aberrant Ig class distribution, GANP has been described to become selectively upregulated in GC B‐cells upon thymus‐dependent antigen immunization. In GCs, AID‐dependent somatic hypermutation (SHM) and CSR generate high‐affinity and class‐switched mature antigen‐specific B‐cells [Kuwahara et al., ]. Indeed, GANP was shown to be required for efficient SHM and generation of high‐affinity B‐cells in mice [Sakaguchi et al., ; Kawatani et al., ] and to promote nuclear import of AID and binding to IgVH ‐regions by GANP–AID complex formation [Maeda et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…By preparing mAbs against GC B cells, we found that a 210‐kDa nuclear protein is selectively up‐regulated in GC B cells upon immunization with TD‐Ag [30]. GANP is encoded by 29 exons in humans and mice.…”
Section: Ganp As a Key Molecule For Regulating Gc B Cell Differentiationmentioning
confidence: 99%
“…The middle portion of GANP is homologous to Saccharomyces cerevisiae Sac3 (suppressor of actin 3) of the THO/TREX2 complex constituting Sac3‐Thp1‐Cdc31‐Sus1 [34] with significant but low (25%) homology at the amino acid level (Sac3‐homology; SAC3/GANP/Nin1/mts3/eIF3p25) (Fig. 2) [30]. In the amino‐(N‐)terminal region, mammalian GANP possesses a unique region homologous to the nucleoporin component of nuclear pore complex [35].…”
Section: Ganp As a Key Molecule For Regulating Gc B Cell Differentiationmentioning
confidence: 99%